Simulative Study of Fuel Performance of Jatropha Curcas Biodiesel versus Palm Oil Biodiesel on Fishing Vessel - Rizal, Teuku Azuar; Umar, Hamdani (Fakultas Teknik Universitas Samudra, 2018)
The paper is investigated the application of Jatropha Curcas biodiesel (JCFAME) as well as Palm biodiesel (PFAME) as an alternative fuel and its performance effect in the diesel engines using Diesel–RK computational simulation. Both alternative fuel was simulated to run in four stroke marine diesel engine with 65 HP and single cylinder engine at 178 g/HP.h fuel consumption rate. The computational model will be running on different diesel fuel mode to simulate and investigate each fuel effect upon engine performance. The result of the simulation shown the effect of each alternative fuel in terms of rpm against brake mean effective pressure (BMEP), rpm against power and rpm against specific fuel consumption (SFC). Also, the comparison will be presented in term of Compression Ratio (CR) against BMEP, CR against SFC and CR against Thermal Efficiency (TE).